War, Terrorism and Authorial Stance: Appraisal Analysis of the Selected Pakistani Fiction in English - Suliman Khan; Hajra Umer; Inayat ullah (University of Chitral Journal of Linguistics and Literature, 2023)
This study focuses on Pakistani English Fiction, specifically examining its portrayal of contemporary terrorism. The research delves into the authorial Stance within this genre, analyzing how writers express their evaluations and stances. Primary data is drawn from two literary works, Bilal Tanweer’s The Scatter Here is Too Great and Nadeem Aslam’s The Blind Man’s Garden, published in 2013. Employing a qualitative approach, the study conducts a detailed analysis of violent acts depicted in these novels, emphasizing the negative portrayal of terrorism. Furthermore, it explores the authors’ techniques in creating poignant atmospheres to evoke reader sympathy for the victims. The theoretical framework employed is the appraisal framework developed by Martin and White (2000), and the novels are analyzed through a close reading technique. This research contributes to a nuanced understanding of how Pakistani English Fiction addresses and critiques the complex and sensitive issue of terrorism in the contemporary world. This study contributes to the broader field of literature and specifically to the genre of terrorism novels.